The European Scleroderma Trials and Research group (EUSTAR) task force for the development of revised activity criteria for systemic sclerosis: derivation and validation of a preliminarily revised EUSTAR activity index. Issue 1 (12th September 2016) - Valentini, Gabriele; Iudici, Michele; Walker, Ulrich A; Jaeger, Veronika K; Baron, Murray; Carreira, Patricia; Czirják, László; Denton, Christopher P; Distler, Oliver; Hachulla, Eric; Herrick, Ariane L; Kowal-Bielecka, Otylia; et al.
Abstract : Background: Validity of European Scleroderma Study Group (EScSG) activity indexes currently used to assess disease activity in systemic sclerosis (SSc) has been criticised. Methods: Three investigators assigned an activity score on a 0–10 scale for 97 clinical charts. The median score served as gold standard. Two other investigators labelled the disease as inactive/moderately active or active/very active. Univariate–multivariate linear regression analyses were used to define variables predicting the 'gold standard', their weight and derive an activity index. The cut-off point of the index best separating active/very active from inactive/moderately active disease was identified by a receiver-operating curve analysis. The index was validated on a second set of 60 charts assessed by three different investigators on a 0–10 scale and defined as inactive/moderately active or active/very active by other two investigators. One hundred and twenty-three were investigated for changes over time in the index and their relationships with those in the summed Medsger severity score (MSS). Results: A weighted 10-point activity index was identified and validated: Δ-skin=1.5 (Δ=patient assessed worsening during the previous month), modified Rodnan skin score (mRss) >18=1.5, digital ulcers=1.5, tendon friction rubs=2.25, C-reactive protein >1 mg/dL=2.25 and diffusing capacity of the lung for CO (DLCO) % predicted <70%=1.0. A cut-off ≥2.5 was found to identify patients with active disease. Changes in the index paralleled those of MSS (p=0.0001). Conclusions: A preliminarily revised SSc activity index has been developed and validated, providing a valuable tool for clinical practice and observational studies.